Catalysts towards cancer risk management action: A longitudinal study of reproductive-aged women with BRCA1/2 mutations. Issue 5 (3rd September 2018) - Werner-Lin, Allison; Ersig, Anne L.; Mueller, Rebecca; Young, Jennifer L.; Hoskins, Lindsey M.; Desai, Ria; Greene, Mark H.
ABSTRACT: Deleterious mutations in BRCA1 or BRCA2 genes increase a woman's lifetime risk of breast and ovarian cancer. Risk management guidelines endorse early detection and prevention behaviors. Despite expressed intent, uptake of these measures remains low. This longitudinal, qualitative study integrated retrospective and prospective data to distinguish factors shaping intent to act from those that are catalysts to taking action to reduce cancer risk. Twelve BRCA1/2 mutation-positive women participating in the National Cancer Institute's Breast Imaging Study aged 18–35 completed two semi-structured interviews three years apart. Researchers completed focused coding to identify points of behavioral intent and action and contextual factors acting as catalysts upon participant narratives. All women shared only two action steps: seeking information about cancer risk and completing genetic testing. The constellation of action steps created a unique action trajectory that was defined, with precise ideas about risk perception and clear behavioral response, or iterative, in which unanticipated life events shifted the speed, accessibility, or order in which risk management and family planning goals were prioritized, planned, or executed. Factors shifting action steps included salient, unanticipated life events, such as infertility, insurance/financial constraints, birth of the last child, or a relative's cancer diagnosis. Focus on cancer morbidity may obfuscate how women prioritize actions, and ignore varied pragmatic, relational, and social factors affecting how intended actions are completed, particularly during the reproductive years. We recommend providers update patients' risk management plans at each visit to assess readiness for next steps and reduce reluctance to discuss, or guilt associated with, change.